Effects of Incorporating Cellulosic Fibers on the Physico-Mechanical Properties of a Basic Magnesium Sulfate Cement - Juan C. A. Molano; Katheryn C. P. Córdoba; Tayná V. Ferreira; Adriano G. S. Azevedo; Holmer Savastano Jr. (Materials Research)
Basic magnesium sulfate cement (BMSC) is a non-conventional binder with advantages such as fire resistance, lightweight properties, and low alkalinity, widely used in lightweight panels. However, the effects of cellulosic fiber incorporation on the hydration mechanisms and mechanical performance of BMSC remains insufficiently explored. This study evaluates the effects of incorporating different dosages of bleached eucalyptus fibers (EB) on the physical, mechanical, and microstructural properties of BMSC composites. Additionally, it examines their influence on hydration reactions and phase formation to determine optimal compositions for construction applications. The composites were analyzed using mechanical tests, X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA) and DIC. Results indicate that the 5-1-7 phase enhances mechanical strength through a space-filling effect, while fiber incorporation increases porosity and alters phase distribution. Higher fiber contents led to increased porosity and a reduction in compressive strength, whereas flexural strength and energy absorption were improved due to fiber-bridging effects. These findings highlight the potential of optimizing fiber dosage to balance strength and toughness in BMSC composites for construction applications.